A NIR light-activated dual drug release system and its preparation method and application
By designing a dual drug release system for NIR photoactivated, the antibacterial and pro-repair effects are achieved using the characteristics of ZIF-8 and PLGA, the problem of incoordinated drug release in the prior art is solved, the efficacy of wound healing is improved and drug resistance is avoided .
Patent Information
- Application Number
- CN202310560049.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-05-18
AI Technical Summary
The existing nanomedicine-loaded materials cannot effectively follow the four stages of wound healing, and cannot efficiently load two drugs with large differences in hydrophilicity and hydrophobicity to achieve controllable sustained release at different times, resulting in weak synergistic effects and inability to Give full play to the medicine's wound healing effect.
A NIR photoactivated dual drug release system was designed to realize the drug by encapsulating the antibiotic ciprofloxacin in ZIF-8, curcumin in PLGA, and Fe3O4 nanoparticles were added, and the degradation of PLGA and NIR photoactivation mechanism was used to realize the drug by using the degradation of PLGA and the NIR photoactivation mechanism. The antibacterial and then the repair effect is combined with the acid-base response of ZIF-8 and the photothermal effect of Fe3O4 to achieve synergistic release of drugs.
It realizes the effect of antibacterial and then promotes repair during wound healing, improves the drug loading rate and utilization efficiency, gives full play to the synergistic effect of antibiotics and curcumin, improves the efficacy of wound healing, avoids drug resistance and Reduce thermal damage to healthy tissues.
Smart Images

Figure CN116898810B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a NIR light-activated dual drug release system and a preparation method and application thereof. Background Art
[0002] The skin is the largest organ in the human body and protects it from injury and invasion of microorganisms. It has a repair function after damage caused by natural disasters or diseases. After the skin is damaged, its structure and function must be restored as soon as possible to maintain the stability of the internal environment. Therefore, the wound healing process begins almost immediately after the skin is injured to avoid bacterial infection of the wound. Once the damaged skin tissue loses its main function as a protective barrier, it is vulnerable to invasion by microorganisms, such as Streptococcus pyogenes, Pseudomonas aeruginosa, and Staphylococcus aureus, which can colonize the wound site, causing infection and may lead to chronic wounds. Antibiotics have been widely used as a widely accepted treatment for bacterial infections. However, the abuse of antibiotics has led to the emergence of many drug-resistant bacteria.
[0003] Many nanomaterials such as silver and metal organic frameworks (MOFs) have been developed as potential antibacterial alternatives. ZIF-8 is a subclass of metal organic frameworks (MOFs). It is a porous material composed of 2-methylimidazole and zinc ions. The coordination bond between the two can dissociate in the acidic microenvironment of bacteria, thereby promoting the release of drugs. The unique skeleton structure of ZIF-8 gives it uniform porosity, adjustable surface functionality and excellent chemical and thermal stability. It is widely used in drug delivery and shows significant antibacterial effects in the treatment of bacterial infections.
[0004] In recent years, there has been increasing interest in the use of photothermal therapy (PTT) for bacterial infections, which uses photothermal converters to convert near-infrared (NIR) light into heat to kill bacteria. Typically, PTT alone may require higher temperatures to completely eliminate bacterial colonies, which may damage adjacent healthy tissue. However, lower temperature activation is not sufficient to completely eradicate stubborn bacterial infections in a rapid period of time. Because the wound healing process is complex and diverse, and is usually divided into four stages: inflammation, migration, proliferation, and remodeling, relying solely on antibiotics or photothermal therapy cannot effectively solve the problem of wound infections caused by bacteria. Therefore, it is urgent to develop a multimodal therapy to fully utilize the advantages of PTT and reduce the emergence of drug resistance.
[0005] Existing studies have reported a NIR / pH dual-stimulus responsive antibacterial preparation based on zeolitic imidazole framework (ZIF-8), which has strong antibacterial activity and combines photothermal heating with enhanced antibiotic delivery. ZIF-8 and polydopamine (PDA) surface modification were used to encapsulate the antibiotic vancomycin to construct a dual-stimulus responsive antibacterial preparation (Van@ZIF-8@PDA). Other scholars have studied and designed an injectable hollow microsphere (HMs) system that can quickly generate local heat activated by near-infrared (NIR) light and control the release of antibiotics through a "molecular switch" in the polymer shell as a combined strategy for the treatment of subcutaneous abscesses. HMs have a shell of poly (D, L-lactic-co-glycolic acid) (PLGA) and an aqueous core composed of vancomycin (Van) and photothermal agent polypyrrole nanoparticles (PPyNP), which have excellent antibacterial effects.
[0006] The efficacy of the natural polyphenolic drug curcumin (Cur) as the main active ingredient of turmeric as a wound healing agent depends on its antioxidant properties, especially its ability to scavenge ROS (reactive oxygen species) and LPx (lipid peroxidation) in the wound area. In addition, curcumin increases cell proliferation, granulation tissue formation, collagen synthesis, collagen maturation and collagen cross-linking. Clinical trials have shown that curcumin is safe, well tolerated and non-toxic even at high doses.
[0007] Polylactic acid-hydroxylactic acid (PLGA) is a polymer formed by the polymerization of lactic acid and glycolic acid. It is an FDA-approved material with the advantages of good biocompatibility, biodegradability, safe and non-toxic degradation products, and controllable degradation rate. It is widely used as a carrier material for drug delivery.
[0008] However, PLGA can only load one drug or two drugs with the same hydrophilic and hydrophobic properties to ensure drug encapsulation and loading. The existing process is still unable to obtain a drug that can not only encapsulate hydrophilic drugs well, but also encapsulate hydrophobic drugs well, and can also achieve controlled sequential sustained release of the two drugs, respectively achieve different stages of drug efficacy, give full play to the synergistic effect of the two drugs, and further improve the effect of the drug delivery system in promoting wound healing.
[0009] Therefore, the above problems need to be solved urgently. Summary of the invention
[0010] The present invention is to solve the above technical problems, thereby providing a NIR light-activated dual drug release system and its preparation method and application. The technical purpose of the present invention is to solve the problem that the existing nano drug-carrying materials cannot well meet the four stages of wound healing and cannot well achieve the drug sustained release effect of first antibacterial and then promoting repair; on the other hand, it solves the problem that the existing nano drug-carrying materials have weak synergistic effects in wound healing and cannot simultaneously and efficiently load two drugs with large hydrophilicity differences to achieve controlled sustained release at different times and give full play to the effect of drugs in promoting wound healing.
[0011] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0012] The present invention first provides a method for preparing a NIR light-activated dual drug release system, comprising the following steps:
[0013] (1) Dissolving ZIF-8 and ciprofloxacin in water, stirring and centrifuging to obtain a ZIF-8 nanomaterial loaded with ciprofloxacin, denoted as ZIF-8@CIP;
[0014] (2) PLGA and curcumin are dissolved in an organic solvent, and then Fe3O4 particles and the ZIF-8@CIP obtained in step (1) are added to form an emulsion after ultrasound, to which polyvinyl alcohol is added to prepare solidified microspheres, which is the NIR light-activated dual drug release system, denoted as PLGA+CUR / Fe3O4+ZIF-8@CIP.
[0015] The above method of the present invention has the following differences and improvements over the prior art method:
[0016] 1. Wound healing stage: The wound healing process is divided into four stages: hemostasis, inflammation, proliferation and remodeling. However, existing repair materials often cannot follow the above four stages of wound healing very well. For example, some of them stop bleeding and reduce inflammation at the same time, while others carry out proliferation and reduce inflammation at the same time. As a result, existing materials fail to follow the four stages of wound healing in promoting wound healing and fail to achieve the best therapeutic effect. In order to fully follow the four stages of wound healing and achieve the special function of first killing bacteria in the second stage, i.e., the inflammatory stage, reducing the harm of inflammation, and then repairing the wound in the third and fourth stages, i.e., the proliferation and remodeling stages, the present invention has successfully designed the NIR light-activated dual drug loading system of the present invention after a lot of exploration and experiments.
[0017] 2. Drug loading sequence: In order to better follow the above four stages of wound healing, the inventors have conducted a lot of exploration and research on the drug loading sequence. In order to obtain a drug release curve that releases antibiotics first and then releases healing agents, the inventors unexpectedly discovered that when the antibiotic ciprofloxacin (CIP) is encapsulated in ZIF-8 and the wound healing agent curcumin (Cur) is encapsulated in PLGA, the corresponding purpose of the present invention can be well achieved. The inventors found that when ZIF-8 is inside PLGA, it does not form hydrogen bonds with PLGA. As PLGA degrades, ZIF-8@CIP breaks away from the encapsulation of PLGA, and its structure collapses under the acidic microenvironment of bacteria, and antibiotics are quickly released to kill bacteria; and when Cur is located in the shell, it forms hydrogen bonds with PLGA. At this time, only when PLGA is completely degraded can Cur be released completely, so the release rate of Cur becomes extremely slow. This dual drug loading structure is well achieved in that the internal antibiotic CIP is released first to play an anti-inflammatory role, and then the external Cur is released to promote wound healing.
[0018] As far as the inventors know, the existing dual drug-carrying material system generally releases the outer drug first, and then further releases the inner drug. In addition, it is worth noting that if the two drugs of the present invention are packaged in reverse, Cur will be completely released first, and then CIP will be further released, which will not achieve the special function of first antibacterial and then promoting repair that the present invention wants to achieve. This packaging method will greatly reduce the effect of promoting wound healing.
[0019] 3. PLGA is a "molecular switch" with a glass transition temperature (Tg) of about 44°C. When the ambient temperature is lower than Tg, the mobility of PLGA molecules is relatively low, resulting in a slow release of drugs from PLGA. However, when the local temperature exceeds Tg, the mobility of the polymer chain increases, which significantly increases the local voids, thereby increasing the drug diffusion rate. Based on this, the dual drug loading system of the present invention achieves good NIR light activation responsiveness.
[0020] When NIR light is absorbed by Fe3O4 nanoparticles encapsulated in PLGA and converted into heat, this local heat first has a bactericidal effect, and secondly, when Fe3O4 is locally heated, the PLGA "molecular switch" is immediately activated, which greatly increases the diffusion rate of the drug. Once PLGA begins to degrade and produce pores, the ZIF-8@CIP encapsulated in PLGA will be stimulated by the acidic microenvironment of the bacteria and released quickly, and the Cur in the shell will be further gradually released completely as PLGA degrades.
[0021] Therefore, the design of the drug delivery system of the present invention can achieve the effect of first reducing inflammation and then promoting repair to the greatest extent, and well follows the corresponding stages of wound healing. In addition, the "molecular switch" effect of PLGA also plays a role in controlling drug release.
[0022] 4. Material design: It can be seen from the examples that in the selection of the content of the three materials PLGA (E1), Fe3O4 (E2), and ZIF-8@CIP (E3), according to the XRD patterns of E1 and E2 ( Figure 2 (Part C) can indirectly reflect that the dual drug loading system designed by the present invention can make these three materials in a dynamic equilibrium relationship (E1 / E2 / E3) that restricts each other. When this dynamic balance is destroyed, such as when the content of E2 and E3 increases slightly, the content of E1 will decrease. At this time, when the content of E1 decreases, it will make it difficult to synthesize microspheres, and E2 and E3 can no longer be well encapsulated in E1, so that the microspheres of the present invention cannot be prepared, and the effect of the present invention cannot be achieved. Therefore, the selection of the amount of materials used in the present invention is precisely because this dynamic balance is well maintained, which produces such a significant therapeutic effect.
[0023] 5. Drug loading method: When loading multiple drugs, traditional drug loading methods can only select drugs of the same nature, or realize the loading of the same hydrophilic and hydrophobic drugs based on the modification of the carrier material. However, Cur selected in the present invention is a hydrophobic drug, and CIP is a hydrophilic drug. It is difficult for the existing carriers to encapsulate the two drugs well at the same time. When selecting drug carriers, it is often only possible to ensure that one of the drugs has a higher drug loading rate and encapsulation rate, while the drug loading rate and encapsulation rate of the other drug will be lower. The method of the present invention solves this technical problem well, successfully synthesizes microspheres with two drugs of different properties, and simultaneously improves the drug loading rate and drug utilization efficiency of the two drugs, so that they can fully exert their respective effects while also playing a good synergistic effect.
[0024] Furthermore, the weight ratio of PLGA, curcumin, Fe3O4 particles and ZIF-8@CIP in step (2) is 12-16:1-2:1-3:2-4.
[0025] Furthermore, the preparation method of ZIF-8 in step (1) is: magnetically stirring Zn(NO3)2·6H2O, 2-methylimidazole and methanol to mix them evenly, then centrifuging at 10000 rpm for 5 min, washing with ethanol, and vacuum drying to obtain the ZIF-8.
[0026] As a preferred solution, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:8.
[0027] Furthermore, the preparation method of the Fe3O4 particles is: dissolving FeCl3·6H2O, sodium acetate and sodium citrate in ethylene glycol, then transferring to an autoclave, heating to 200°C and continuing the reaction for 10 hours, separating the product with a magnet after the reaction, repeatedly washing the product, and vacuum drying to obtain the Fe3O4 particles.
[0028] As a preferred solution, the molar ratio of FeCl3·6H2O, sodium acetate and sodium citrate is 25:146:7.7.
[0029] Furthermore, the operation of centrifugation after stirring in step (1) is: magnetic stirring for 24 hours, and then centrifugation at 10000 rpm for 5 minutes.
[0030] Furthermore, in step (1), the ZIF-8@CIP is washed with ethanol for three times and then vacuum dried; in step (2), the PLGA+CUR / Fe3O4+ZIF-8@CIP is washed with RO water for three times and then vacuum dried.
[0031] Furthermore, the organic solvent in step (2) includes at least one of dichloromethane, chloroform, acetone, ethyl acetate, hexafluoroisopropanol or acetonitrile.
[0032] Furthermore, the operation of preparing the solidified microspheres in step (2) is: the emulsion is homogenized by mechanical stirring at a rate of 10000 rpm for 1 min, and then poured into a 0.4 wt % PVA solution and mechanically stirred at 300 rpm for 4 h.
[0033] The second purpose of the present invention is to provide a NIR light activated dual drug release system prepared by the above method. The drug release system can well meet the four stages of wound healing, achieve the effect of first antibacterial and then promoting repair, and its synergistic repair effect is excellent.
[0034] The second object of the present invention is to provide an application of the above-mentioned NIR light-activated dual drug release system, which is to use it as a drug-carrying material as a drug to promote wound healing.
[0035] The beneficial effects of the present invention are as follows:
[0036] (1) The present invention makes full use of the advantages of nanomaterial ZIF-8, wound healing agent curcumin (Cur) and photothermal therapy (PTT) to design a new antibacterial and repair-promoting micro-composite material. The existing methods cannot achieve efficient loading of two drugs with different hydrophilicity and hydrophobicity at the same time, while the method of the present invention well achieves efficient loading of antibiotic ciprofloxacin (CIP), wound healing agent Cur and photothermal agent Fe3O4.
[0037] (2) ZIF-8 has acid-base responsiveness, and the coordination between zinc and imidazolate ions dissociates at a pH of 5.0-6.0, thereby promoting the release of drugs. Under acidic conditions and 808nm infrared laser irradiation, the CIP loaded by the nanoparticle ZIF-8 in the dual drug-loaded microspheres is first released to kill bacteria in the infected wound; then, PLGA slowly releases CUR to promote wound repair, achieving a good dual therapeutic effect of first sterilization and then promotion of repair. However, the existing drug-loading system often does not follow the process of first sterilization and then promotion of repair when promoting wound healing, which limits the efficacy.
[0038] (3) The present invention also takes advantage of photothermal therapy (PTT) and uses the photothermal agent Fe3O4. Compared with traditional antibiotic therapy, it has the advantages of avoiding drug resistance and causing minimal thermal damage to healthy tissues. Fe3O4 can not only provide photothermal effects to increase the temperature of the material and accelerate the drug release rate; it can also provide magnetism to adsorb the microspheres to the wound site to prevent them from free diffusion everywhere, playing a good synergistic role in promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the synthesis of P+CUR / F+Z@CMCs according to an embodiment of the present invention;
[0040] Figure 2 It is the optimization of the content of Fe3O4 and ZIF-8@CIP; (A1-A3) Inverted microscope pictures of PLGA / (10mg, 20mg and 30mg)Fe3O4; (B1-B3) Particle size distribution of microspheres after treatment of (A1-A3); (C) XRD spectrum, where (a) is Fe3O4, (b, c, d) are PLGA / (10mg, 20mg and 30mg)Fe3O4 respectively; (e) is PLGA; (D) Drug loading rate and encapsulation rate of PLGA / ZIF-8@CIP, DLC is on the left and DLE is on the right;
[0041] Figure 3 The photothermal performance of P+CUR / F+Z@CMCs; (A) Temperature change curves of different materials after 5 minutes of NIR irradiation; (B) Temperature change curves of different materials under NIR (2.0W / cm 2 ) Real-time infrared thermal image after 5 minutes of irradiation; (C) Temperature change curves of P / F+Z+CURMCs with different concentrations (0, 100, 250, 500, 1000 and 2000 μg / mL) under NIR irradiation for 5 minutes; (D) Real-time infrared thermal image corresponding to (C);
[0042] Figure 4The in vitro antibacterial effects of different MCs prepared in the examples; (A) Photos of Staphylococcus aureus colonies in agar plates with or without NIR irradiation of P+CUR / F+ZMCs at different concentrations (0, 100, 250, 500 and 1000 μg / mL); (B) Photos of Staphylococcus aureus colonies in agar plates with or without NIR irradiation of different materials; (C) Summary of bacterial activity after treatment with (A); (D) Summary of bacterial activity after treatment with (B). DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0044] Example 1
[0045] 1. Experimental methods:
[0046] (1) Synthesis of ZIF-8, Fe3O4 and ZIF-8@CIP
[0047] ZIF-8(Z): Zn(NO3)2·6H2O (372 mg), 2-methylimidazole (820 mg) and methanol (30 mL) were magnetically stirred for two hours to mix them evenly, centrifuged at 10000 rpm for 5 min, washed with ethanol three times, and vacuum dried to obtain the finished product, namely ZIF-8 (a zeolitic imidazole framework material).
[0048] Fe3O4 microspheres (F): FeCl3·6H2O (6.8 g), sodium acetate (12.0 g) and sodium citrate (2.0 g) were dissolved in 200 mL of ethylene glycol to obtain a uniform yellow solution, which was transferred to an autoclave and then heated to 200°C for 10 h. After the reaction, the product was separated by a magnet, washed repeatedly with RO water and ethanol several times, and vacuum dried to obtain the finished product.
[0049] ZIF-8@CIP (Z@C): ZIF-8 (226 mg, Z) and CIP (100 mg, C) were dissolved in RO water (100 mL), magnetically stirred for 24 h, centrifuged at 10,000 rpm for 5 min, washed three times with RO water, and vacuum dried to obtain the finished product.
[0050] (2) Synthesis of PLGA+CUR / Fe3O4+ZIF-8@CIP microspheres (MCs)
[0051] 160 mg PLGA (P) and 20 mg curcumin (CUR) were dissolved in 2.5 mL dichloromethane, 30 mg Fe3O4 (F) and 40 mg ZIF-8@CIP (Z@C) were dissolved in 1.5 mL RO water, ultrasonically dispersed evenly, and then added to the PLGA and curcumin emulsion, ultrasonicated for 2 min to form an oil-in-water (W1 / O) emulsion, 6.5 mL 4 wt% PVA solution was added, and then mechanically stirred at a rate of 10,000 rpm for 1 min to form a water-in-oil-in-water (W1 / O / W2) emulsion. The solution was poured into 0.4 wt% PVA solution (100 mL) and mechanically stirred at low speed (300 rpm) for 4 h to remove the organic solvent and solidify the microspheres. The product was then separated by a magnet, washed with RO water three times, and freeze-dried for 24 h to obtain the finished product, which was stored at -4 °C to obtain PLGA+CUR / Fe3O4+ZIF-8@CIP(P+CUR / F+Z@C)MCs.
[0052] (3) Photothermal effect of PLGA+CUR / Fe3O4+ZIF-8@CIPMCs
[0053] By using 808nm infrared laser at 2.0W / cm 2 The power density was irradiated for 5 min with concentrations of 0, 100, 250, 500, 1000 and 2000 μg / mL P+CUR / F+Z@CMCs, and the temperature was recorded every 30 seconds using an infrared thermal imager to study the photothermal performance of P / F+Z@C at different concentrations. The experimental methods for the control groups of PLGA, Fe3O4, CIP, ZIF-8, PLGA-coated Fe3O4 and CIP were the same as above.
[0054] (4) Antibacterial experiment of PLGA+CUR / Fe3O4+ZIF-8@CIPMCs
[0055] In order to study the antibacterial effect of P+CUR / F+Z@C, the drug resistance of Gram-positive bacteria represented by Staphylococcus aureus was tested. 5 CFU·mL -1 Staphylococcus aureus was diluted with PBS (pH 7.4 or pH 5.0) and cultured in a 48-well plate. A series of P+CUR / F+Z@CMCs suspensions in the same buffer were added to form final concentrations of 0, 100, 250, 500, and 1000 μg / mL. After incubation for 12 hours, the cells were illuminated with an 808 nm infrared laser (2 W·cm -2 ) for 5 minutes, and then incubate at 37°C for 10 hours before plating. The bacterial survival rate was calculated using the following formula:
[0056] Survival rate = C / C0 × 100%;
[0057] Where: C is the average number of bacterial colonies after treatment, and C0 is the average number of bacterial colonies in the control experiment.
[0058] 2. Experimental results:
[0059] The experimental data results of the present invention are analyzed as follows:
[0060] (I) The preparation scheme diagram, material optimization, photothermal performance and in vitro antibacterial effect experimental data of P+CUR / F+Z@CMCs in the above examples are shown in Figures 1 to 4 .
[0061] Figure 2 Parts A and B in Figure 2 show the morphology and size distribution of PLGA / Fe3O4 composite microspheres. As can be seen, all samples are spherical, and the sizes of more than 100 microspheres were measured from inverted fluorescence microscope images using the software ImageJ. Figure 2 As shown in parts B1-B3, the size of PLGA / Fe3O4 composite microspheres with Fe3O4 mass of 10, 20 and 30 mg was 18.91±8.98, 17.91±8.69 and 17.48±8.56 μm, respectively, while the PLGA mass was constant. The similar size means that the encapsulated Fe3O4 nanoparticles had no effect on the size of the composite microspheres.
[0062] XRD patterns show the crystal structures of PLGA, PLGA / Fe3O4 composite microspheres and Fe3O4 nanoparticles. Figure 2 Part C (ad) shows six characteristic peaks at 30.5° (220), 35.84° (311), 43.46° (400), 53.90° (42), 57.38° (511) and 62.90° (440), which are consistent with the standard XRD data card of Fe3O4 (JCPDS No. 19-06290). Figure 2 The PLGA in the middle C part (g) has a broad and clear amorphous peak at about 15°. As the weight ratio of PLGA to Fe3O4 increases, the stability of the PLGA / Fe3O4 composite microspheres becomes more obvious. These results indicate that all the synthesized products retain the spinel structure of magnetite crystals. The drug loading rate of PLGA microspheres increases with the increase of ZIF-8@CIP content ( Figure 2 Therefore, 30 mg of Fe3O4 and 40 mg of ZIF-8@CIP were used in subsequent experiments to maintain a dynamic balance between PLGA and the two.
[0063] (ii) To systematically evaluate the photothermal performance, an infrared thermal imager was used under constant NIR irradiation (808 nm, 2 W / cm 2) to monitor the microspheres dispersed in PBS. Figure 3 As shown in part A, the corresponding heating curve is Figure 3 As shown in part B. The results show that the temperature of Fe3O4 nanoparticles alone can reach 69°C after 5 minutes of irradiation, while the temperature of other particles without Fe3O4 remains almost unchanged after 5 minutes of irradiation. As the concentration of P+CUR / F+Z@CMCs increases, the temperature of the solution gradually increases within 5 minutes, while the temperature of the PBS group does not change. 1000μg / mL P+CUR / F+Z@C microspheres can reach about 50°C within 5 minutes under near-infrared radiation. Studies have shown that local temperature increases induced by near-infrared can destroy bacterial cell membranes, denature bacterial proteins, and cause bacterial death. Therefore, a microsphere concentration of 1000μg / mL was selected for subsequent studies, including animal experiments.
[0064] The drug release from PLGA microspheres mainly includes two mechanisms: diffusion of drug molecules and degradation of the polymer matrix. The faster the degradation, the faster the drug release. The degradation of PLGA is the hydrolysis of ester bonds in the polymer backbone, and heating can accelerate its degradation. At the same time, the heat generated by the photothermal effect can also promote the diffusion of drugs, which helps to increase drug release. Therefore, the drug release is accelerated under NIR irradiation and the acidic microenvironment of bacteria, which may be due to the release of embedded CUR caused by the glass-rubber transition and the thermal destruction of the PLGA micromatrix. When PLGA reaches Tg, its diffusion coefficient increases significantly by 3 orders of magnitude. Due to the high porosity and porous structure of ZIF-8, the drug CIP can be quickly released under NIR / pH dual stimulation. These phenomena indicate that P+CUR / F+Z@CMCs exhibits strong drug release to NIR, especially under acidic conditions.
[0065] The above results are consistent with previous reports that acidic conditions lead to the degradation of ZIF-8. Therefore, it can be concluded that the NIR-induced high temperature of Fe3O4 enhances the drug release under acidic conditions and that NIR radiation can be used as a switch to control drug release from P+CUR / F+Z@CMCs.
[0066] (III) To evaluate the in vitro antibacterial ability of P+CUR / F+Z@CMCs, the materials were incubated with Staphylococcus aureus under conditions of exposure or not to NIR, and plate counts were performed. Figure 4As shown in parts A and C, the colony counts in the PBS group were quite high regardless of irradiation, and no significant difference was found in the inhibition of bacterial growth on the plates treated with PBS, indicating that NIR alone did not have a killing effect on bacteria. The survival rate of Staphylococcus aureus was 52.68% when NIR was used for 5 minutes in the P / FMCs group. This is because the heat generated under NIR irradiation has a killing effect on bacteria, the degradation of PLGA is accelerated, and its degradation products also have antibacterial properties, thereby enhancing the antibacterial ability. The bacterial survival rate of the P+CUR / FMCs group under NIR irradiation was 38.24%, which is higher than that of the P / FMCs group. This is because the drug CUR also has killing effects on bacteria.
[0067] In addition, the experimental results showed that with the increase of concentration in the P+CUR / F+Z@CMCs group, the bactericidal effect of the NIR group gradually increased. The antibacterial effect reached 10.81% at a concentration of 500 μg / mL, and the bacterial survival rate was 0% at a concentration of 1000 μg / mL, indicating that P+CUR / F+Z@CMCs showed significant antibacterial potential under NIR.
[0068] Comparative Example 1
[0069] According to the method of Example 1, ZIF-8 and curcumin were first dissolved and mixed, and then PLGA and ciprofloxacin were dissolved and mixed, and Fe3O4 particles were added to prepare microspheres. The results showed that the microspheres first completely released curcumin and then released ciprofloxacin, which played the role of healing first and then sterilization, which was not in line with the process of wound healing.
Claims
1. A method for preparing a NIR light-activated dual drug release system, characterized in that: The following steps are involved: (1) Dissolving ZIF-8 and ciprofloxacin in water, stirring and centrifuging to obtain a ZIF-8 nanomaterial loaded with ciprofloxacin, denoted as ZIF-8@CIP; (2) PLGA and curcumin are dissolved in an organic solvent, and then Fe3O4 particles and ZIF-8@CIP obtained in step (1) are added to form an emulsion after ultrasound, and polyvinyl alcohol is added thereto to prepare solidified microspheres, which is the NIR light-activated dual drug release system, recorded as PLGA+CUR / Fe3O4+ZIF-8@CIP.
2. The preparation method according to claim 1, characterized in that: The weight ratio of PLGA, curcumin, Fe3O4 particles and ZIF-8@CIP in step (2) is 12-16:1-2:1-3:2-4.
3. The preparation method according to claim 1, characterized in that: The preparation method of ZIF-8 described in step (1) is: magnetically stir a mixture of Zn(NO3)2·6H2O, 2-methylimidazole and methanol to mix them evenly, then centrifuge at 10000rpm for 5min, wash with ethanol, and vacuum dry to obtain the ZIF-8; the molar ratio of Zn(NO3)2·6H2O and 2-methylimidazole is 1:
8.
4. The preparation method according to any one of claims 1 to 3, characterized in that The preparation method of the Fe3O4 particles is as follows: FeCl3·6H2O, sodium acetate and sodium citrate are dissolved in ethylene glycol, then transferred to an autoclave, heated to 200°C for continuous reaction for 10 hours, and after the reaction is completed, the product is separated by a magnet, the product is repeatedly washed, and vacuum dried to obtain the Fe3O4 particles; the molar ratio of the FeCl3·6H2O, sodium acetate and sodium citrate is 25:146:7.
7.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The stirring and centrifuging operation in step (1) is: firstly magnetic stirring for 24 hours, and then centrifuging at 10000 rpm for 5 minutes.
6. The preparation method according to any one of claims 1 to 3, characterized in that: In step (1), the ZIF-8@CIP is washed with ethanol for three times and then vacuum dried; in step (2), the PLGA+CUR / Fe3O4+ZIF-8@CIP is washed with pure water for three times and then vacuum dried.
7. The preparation method according to any one of claims 1 to 3, characterized in that: The organic solvent in step (2) includes at least one of dichloromethane, chloroform, acetone, ethyl acetate, hexafluoroisopropanol or acetonitrile.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The operation of preparing the solidified microspheres in step (2) is as follows: the emulsion is homogenized at a rate of 10000 rpm for 1 min, and then poured into a 0.4 wt % PVA solution and mechanically stirred at 300 rpm for 4 h.
9. The NIR light activated dual drug release system prepared by the method according to any one of claims 1 to 8.
10. Use of the NIR light activated dual drug release system according to claim 9, characterized in that: It is used as a drug-carrying material to prepare drugs that promote wound healing.
